The Shaping of Professional Identities : Revisiting Critical Event Narrative Inquiry - Elin Eriksen Ødegaard; Mette Bøe Lyngstad; Schei, Tiri Bergesen (Critical Storytelling, 2024)
This thought-provoking research anthology adopts a postmodern stance and fills in a gap of knowledge for the education of professional development in teacher education, health sciences and the arts. Allowing subjectivity and multiple voices, the authors add to the intimate and negotiated knowledge of being and becoming - indigenous, architect, mother, teacher, health researcher, and supervisor. In fifteen chapters, the authors share knowledge of pain and reward in critical events in the realm of professional identity formation. The book provides a selection of personal and far-reaching stories and adds to the reflexivity of memories of critical events. Contributors are: Geir Aaserud, Åsta Birkeland, Bodil H. Blix, Sidsel Boldermo, Mimesis Heidi Dahlsveen, Nanna Kathrine Edvardsen, Rikke Gürgens Gjærum, Tona Gulpinar, Carola Kleemann, Tove Lafton, Mette Bøe Lyngstad, Elin Eriksen Ødegaard, Anna-Lena Østern, Alicja R. Sadownik, Tiri Bergesen Schei and Vibeke Solbue.